'To die with dignity or to be supplanted by the standard'. Empowerment and inclusive practices of urban new speakers of Aragonese. Issue 1 (2nd January 2022) - Gimeno-Monterde, Chabier; Sorolla, Natxo
ABSTRACT: Aragonese is a threatened Romance language immersed in a historical process of substitution by Spanish, the official language. The number of speakers who maintained its transmission to younger generations, mainly in rural areas, has extremely declined over the last century. In the meantime, revitalisation efforts have incorporated new speakers, especially in urban areas. Due to a weak and conflicting standardisation and institutionalisation of the language, as in other threatened languages, the new speakers are located between three poles: the supremacist position of the official language; the authenticity position highlighting the native varieties; or the legitimisation of supralocal varieties in a context with a hierarchical and conflicted management of revitalisation. The analysis of the interviews allows us to categorise the discourses and establish profiles of new speakers, according to their ideologies and declared practices. The results show a polarisation of the urban new speakers' discourses, with disputes about the legitimacy of supralocal varieties, the contact with native speakers, or the forms of acquisition of the language. All these questions converge in the central academic debate about the Aragonese as a threatened language, and the new speakers and the proactivity not only as the future of the language, but also as its present.